Do β-Blockers Cause Depression?: Systematic Review and Meta-Analysis of Psychiatric Adverse Events During β-Blocker Therapy. Issue 5 (15th March 2021) - Riemer, Thomas G.; Villagomez Fuentes, Linda E.; Algharably, Engi A.E.; Schäfer, Marie S.; Mangelsen, Eva; Fürtig, Marc-Alexander; Bittner, Nadine; Bär, Annalena; Zaidi Touis, Laila; Wachtell, Kristian; Majic, Tomislav; Dinges, Martin J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : β-Blockers are important drugs in the treatment of cardiovascular diseases. They are suspected of inducing various psychiatric adverse events (PAEs), particularly depression, affecting cardiovascular morbidity and mortality. We performed a systematic search for double-blind, randomized controlled trials investigating β-blockers to analyze the risk of PAEs or withdrawal of therapy due to PAEs. We extracted the frequencies of PAEs and rates of withdrawals and reviewed them to the number of exposed patients. For β-blockers versus placebo or other active treatment, we calculated odds ratios for individual PAEs and withdrawal rates. We retrieved overall 285 eligible studies encompassing 53 533 patients. The risk of bias was judged to be high in 79% of the studies. Despite being the most frequently reported PAE with a total of 1600 cases, depression did not occur more commonly during β-blockers than during placebo (odds ratio, 1.02 [95% CI, 0.83–1.25]). β-Blocker use was also not associated with withdrawal for depression (odds ratio, 0.97 [95% CI, 0.51–1.84]). Similar results were obtained for comparisons against active agents. Among other PAEs, only unusual dreams, insomnia, and sleep disorder were possibly related to β-blocker therapy. In conclusion, this analysis of large-scale data from double-blind, randomized controlled trials does not support an association between β-blocker therapy and depression. Similarly, no effect for β-blockers was found for other PAEs, with the possible exceptions of sleep-related disorders. Consequently, concerns about β-blockers' impact on psychological health should not affect their use in clinical practice.